Effect of Cutting Parameter Variation on Drilling of AISI 1045: Experimental and Simulation - Yanuar Burhanuddin (JURNAL MECHANICAL, 2010)
This work is focused on the study of the effect of spindle speed and feed rate on the tool temperature distribution in the drilling of AISI-1045 steel. The e data were collected under different cutting conditions. The maximum tool temperature is predicted during the drilling using finite element simulation techniques. The predicted temperature was compared to the measured temperature. The result shows the finite element simulation is reasonable.  Analyses show that the range of temperature from 157 °C to 288 °C. The difference between measured temperature and simulated temperature are in the range of 17-38%. The s increased in accordance with the increasing of cutting speed and feed. Keywords: drilling, spindle speed, feed, tool edge, maximum temperature